FINANCIAL AND ECONOMIC SECURITY OF INVESTMENT DEVELOPMENT OF DOMESTIC TRADE IN THE CONDITIONS OF WAR AND POST-WAR RECONSTRUCTION OF UKRAINE’S ECONOMY - SVYDRUK, Irena; HRYNIV, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study is dedicated to the identification of factors for ensuring the financial and economic security of domestic trade in the conditions of challenges and threats of war and post-war recovery of the economy of Ukraine. The objective function of investment activity is implemented by strengthening competitive positions and reducing vulnerability to adverse financial factors, which actualizes the identification of factors of financial and economic security of investment development of domestic trade. Solving problems in the spheres of management of trade and technological processes and development of trade infrastructure require a reduction of investment and business risks. It has been found that the investment goals of restoring domestic trade in terms of modernizing the management of the development of business entities are complicated in the conditions of military challenges and threats inherited from pre-war times. The identified cause-and-effect relationships between the categories of financial and economic and investment security allow the simultaneous consideration of the interests of the state and subjects of trade activity. It is proved that the exogenous dimension of the eco-state of the post-war recovery of Ukraine causes changes in the perception of the investment component of the financial and economic security of internal trade, supplementing it with the dimension of opportunities and threats of investment interaction. The proposed approach allows you to move away from the linear progression of the usual extrapolation methods and take into account assumptions about different future scenarios, developing a consensus on the innovative transformation of domestic trade despite the regional unevenness of the post-war preservation of trade infrastructure and different dynamics of innovative shifts. It is proposed to supplement the static characteristics of the achieved level of financial and economic security with the dynamic characteristics of investment performance, which will allow more effectively to generate areas of innovative use of available finances. It is advisable to carry out further studies of the eco-state of the post-war recovery of domestic trade in the direction of clarifying the indicative parameters of the assessment and developing countermeasures against systemic investment risks.